(untitled) (Revista Contexto & Educação, 2024)
Reading and writing are essential skills for satisfactory learning in the student’s school life. Given this context, this article aims to analyze the look of reality experienced by a teacher and five students of the 5th year of Elementary School at a Municipal School in Macapá-AP. The theoretical foundation offered a basis for conducting the research, providing subsidies that contributed significantly to the reflection on issues related to the understanding of learning difficulties in reading and writing. This is a qualitative research through a case study that used a semi-structured interview applied to a 5th grade teacher as a data collection instrument and direct observation with four students who have reading and writing difficulties. The results indicate that, in order to solve the difficulties, it is necessary a joint effort of the entire school team, as well as a differentiated pedagogical practice so that, at the end of each year, the student has acquired the skills and competences necessary to continue his studies.